Genome-Wide Screen for Oxalate-Sensitive Mutants of Saccharomyces cerevisiae - Cheng, V. (American Society for Microbiology (ASM), 2007)
Oxalic acid is an important virulence factor produced by phytopathogenic filamentous fungi. In order to discover yeast genes whose orthologs in the pathogen may confer self-tolerance and whose plant orthologs may protect the host, a Saccharomyces cerevisiae deletion library consisting of 4,827 haploid mutants harboring deletions in nonessential genes was screened for growth inhibition and survival in a rich medium containing 30 mM oxalic acid at pH 3. A total of 31 mutants were identified that had significantly lower cell yields in oxalate medium than in an oxalate-free medium. About 35% of these mutants had not previously been detected in published screens for sensitivity to sorbic or citric acid. Mutants impaired in endosomal transport, the rgp1Δ, ric1Δ, snf7Δ, vps16Δ, vps20Δ, and vps51Δ mutants, were significantly overrepresented relative to their frequency among all verified yeast open reading frames. Oxalate exposure to a subset of five mutants, the drs2Δ, vps16Δ, vps51Δ, ric1Δ, and rib4Δ mutants, was lethal. With the exception of the rib4Δ mutant, all of these mutants are impaired in vesicle-mediated transport. Indirect evidence is provided suggesting that the sensitivity of the rib4Δ mutant, a riboflavin auxotroph, is due to oxalate-mediated interference with riboflavin uptake by the putative monocarboxylate transporter Mch5.